2012
DOI: 10.1188/12.onf.e233-e240
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Patients With Cancer Who Develop Venous Thromboembolism: An Exploratory Study

Abstract: Study findings suggest that patient education about VTE would be useful for the initial reaction and subsequent coping phases of VTE, thus representing an important target area for nursing intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(70 citation statements)
references
References 33 publications
2
68
0
Order By: Relevance
“…Whilst PELICAN, similarly, identified limited patient knowledge about the risk of VTE, it also suggested this lack of awareness may delay the diagnosis and subsequent treatment of CAT. It is commonplace for chemotherapy patients to be advised of the signs and symptoms of neutropenic sepsis and to be given clear instructions of what to do in such an event 20. Since CAT is the most common cause of chemotherapy-related mortality, it would seem appropriate to afford similar emphasis on CAT awareness as is seen with neutropenic sepsis 5.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst PELICAN, similarly, identified limited patient knowledge about the risk of VTE, it also suggested this lack of awareness may delay the diagnosis and subsequent treatment of CAT. It is commonplace for chemotherapy patients to be advised of the signs and symptoms of neutropenic sepsis and to be given clear instructions of what to do in such an event 20. Since CAT is the most common cause of chemotherapy-related mortality, it would seem appropriate to afford similar emphasis on CAT awareness as is seen with neutropenic sepsis 5.…”
Section: Discussionmentioning
confidence: 99%
“…Increased mortality [9] • Morbidity caused by symptoms of pulmonary embolism or deep-vein thrombosis [10,11] • Reduced quality of life [12] • Interruption of cancer treatment [13,14] • Financial consequences [15,16] Long Term Consequences…”
mentioning
confidence: 99%
“…26 Furthermore, a Canadian study identified that patients with CAT experienced frightening symptoms, which they recognised as potentially life-threatening and requiring urgent treatment. 27 Patients perceived CAT as an additional burden to their cancer and associated treatments, and while some felt the VTE was insignificant compared with their cancer diagnosis, others viewed it as a setback in their cancer journeys. 27 Treatment of VTE involves 5 days' anticoagulation therapy with LMWH and subsequently 3-6 months' warfarin.…”
Section: Background and Rationalementioning
confidence: 99%
“…27 Patients perceived CAT as an additional burden to their cancer and associated treatments, and while some felt the VTE was insignificant compared with their cancer diagnosis, others viewed it as a setback in their cancer journeys. 27 Treatment of VTE involves 5 days' anticoagulation therapy with LMWH and subsequently 3-6 months' warfarin. 2,3 However, patients with cancer experience higher rates of further thrombotic and haemorrhagic events.…”
Section: Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation